Framework Administered Account for Selected Fund Activities : United States Subaccount for Selected Fund Activities. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Niger's macroeconomic performance and policies through end-January 2010 were assessed in the IMF Country Report No. 10/146, issued following the completion of the third program review under the arrangement under the Extended Credit Facility (ECF) from the IMF. Since the military intervention in February, the near-term growth outlook has weakened, reflecting the intensity of the food crisis and some contraction in public spending, but the outlook for 2011 is broadly favorable provided that budgetary policies remain appropriately cautious, that normal weather conditions prevail, and that donor support for Niger picks up.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: PP; Subaccount; Terms and Conditions Of The Subaccount; Terms and Conditions; United States Government Agency; United States